Les monologues voilés (Axe sud, 2010)
Véritable blockbuster, Les Monologues Voilés ont rencontré un succès phénoménal dès la création au Théâtre de Poche de Bruxelles. Depuis, le spectacle a été joué plus de 180 fois - à guichets fermés - en Belgique et à Paris.Le spectacle nous propose 12 monologues d'une exceptionnelle intensité, drôles, poétiques, émouvants nous offrant le rare privilège d'entrer dans l'intimité de femmes musulmanes, sans fausse pudibonderie ni voyeurisme. [source jaquette].
Place: Paris Publication Title: Scènes & Cies
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; approches et analyses; arabie saoudite; arts; asie; corps; cours; discipline; europe; féminisme islamique; irak; maroc; militance; pakistan; pays-bas; premier cycle; pédagogie; périodes historiques; régions géographiques; sex2283; somalie; thématiques; théâtre; turquie; égypte

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires